Phenotypic and genetic divergence in a cold-adapted grasshopper may lead to lineage-specific responses to rapid climate change - Meza-Joya FL; Morgan-Richards M; Trewick SA (John Wiley and Sons Ltd, 2024)
Aim: Species responses to global warming will depend on intraspecific diversity, yet studies of factors governing biogeographic patterns of variability are scarce. Here, we investigate the evolutionary processes underlying genetic and phenotypic diversity in the flightless and cold-adapted grasshopper Sigaus piliferus, and project its suitable space in time. Location: Te Ika-a-Māui Aotearoa—North Island of New Zealand. Methods: We used mitochondrial sequences to investigate population connectivity and demographic trends using phylogeographic tools and neutrality statistics. Metric data were used to document phenotypic variation using naïve clustering. We used niche metrics to assess intraspecific niche variation, and niche modelling to investigate suitability under past and future scenarios. Multiple matrix regressions with randomization explored the processes contributing to phenotypic differentiation among grasshopper populations. Results: Niche models and demographic analyses suggest suitable space for this grasshopper was more restricted during glacial than interglacial stages. Genealogical relationships among ND2 haplotypes revealed a deep north–south split partly concordant with phenotypic and niche variation, suggesting two ecotypes that have mixed during recolonisation of the central volcanic region. Multiple matrix regressions with randomization indicate a link between climate and phenotypic differentiation inferred from leg and pronotum dimensions but not pronotum shape. Niche projections predict severe habitat reduction due to climate warming. Main conclusions: The current distribution and intraspecific diversity of S. piliferus reflect complex biogeographical scenarios consistent with Quaternary climates and volcanism. Phenotypic divergence appears adaptive. Current levels of genetic and phenotypic variation suggest adaptive potential, yet the pace of anthropogenic warming over the next 50 years could result in small populations that may collapse before adapting. Differences in niche features between diverging intraspecific lineages suggest distinct responses to climate change, and this has implications for prioritising conservation actions and management strategies.
Keywords: adaptation; conservation; intraspecific variation; Quaternary climates and volcanism; range shifts